An individualized medication model of sodium valproate for patients with bipolar disorder based on machine learning and deep learning techniques - Zheng, Ping; Yu, Ze; Mo, Liqian; Zhang, Yuqing; Lyu, Chunming; Yu, Yongsheng; Zhang, Jinyuan; Hao, Xin; Wei, Hai; Gao, Fei; Li, Yilei (Frontiers in Pharmacology, 2022)
Valproic acid/sodium valproate (VPA) is a widely used anticonvulsant drug for maintenance treatment of bipolar disorders. In order to balance the efficacy and adverse events of VPA treatment, individualized dose regimen is necessary. The aim of this study was to establish an individualized medication model of VPA for patients with bipolar disorder based on machine learning and deep learning techniques. Sequential Forward Selection algorithm was applied for selecting feature subset, Random Forest was used for interpolating missing values. Then we compared 9 models using XGBoost, LightGBM, CatBoost, Random Forest, GBDT, SVM, Logistic Regression, ANN and TabNet, and CatBoost was chosen to establish the individualized medication model with the best performance (accuracy=0.85, AUC=0.91, sensitivity=0.85, and specificity=0.83). Three important variables that correlated with VPA daily dose included VPA TDM value, antipsychotics, and indirect bilirubin. SHapley Additive exPlanations was applied to visually interpret their impacts on VPA daily dose. Lastly, confusion matrix presented that predicting daily dose of 0.5 g VPA had a precision of 55.56% and recall rate of 83.33%, and predicting daily dose of 1 g VPA had a precision of 95.83% and recall rate of 85.19%. In conclusion, the individualized medication model of VPA for patients with bipolar disorder based on CatBoost had a good prediction ability, which provides guidance for clinicians to propose the optimal medication regimen.